2009
DOI: 10.1007/bf03179069
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of doxycycline in ischemia/reperfusion injury on kidney

Abstract: Renal ischemia and reperfusion injury is the major cause of acute renal failure and may also be involved in the development and progression of some forms of chronic kidney disease. The aim of this study was to evaluate whether doxycycline, a member of the tetracycline family of antibiotics, protects kidney tissue or not. 36 Sprague-Dawley rats (200-250 g) were used. The animals were divided into three groups: control, ischemia/reperfusion and ischemia/reperfusion+doxycycline group. Rats were subjected to renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…I/R induces oxidative stress in the kidneys, which causes the enhancement of the reactive oxygen products and the disappearance of the antioxidant defense system (8). In the present study, I/R injury was created in the renal tissue of rats and it was found that the renal damage created by I/R was significantly decreased by quercetin treatment.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…I/R induces oxidative stress in the kidneys, which causes the enhancement of the reactive oxygen products and the disappearance of the antioxidant defense system (8). In the present study, I/R injury was created in the renal tissue of rats and it was found that the renal damage created by I/R was significantly decreased by quercetin treatment.…”
Section: Discussionsupporting
confidence: 50%
“…Apoptosis is a form of programmed cell death, and in this way cells that have been damaged in the organism are removed without harming their environment (8,9). p53 is a tumor suppressor gene that plays an important role in cell cycle control and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The function and structure of TECs depend on the establishment and maintenance of surface membrane polarity. Ischemic acute renal failure has been shown to cause apical membrane disruption, collapse of microvilli, and loss of cell polarity in proximal tubules [2,3,4,5]. A growing body of literature has demonstrated that the actin cytoskeleton plays a role in the regulation of several signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…El uso de doxiciclina, tanto en animales infectados por E. canis como en animales sanos, demostró disminuir progresivamente la concentración de creatinina sérica que sugiere un efecto nefroprotector (5). Algunos estudios han descrito, que a altas dosis el uso de doxiciclina puede bajar la tasa de filtración glomerular causando estados de isquemia en la arteriola eferente que puede llegar a inducir el incremento en los valores de creatinina sérica, una de las teorías es la reducción en el estrés oxidativo, disminuyendo los niveles de citoquinas e inhibición de la actividad de metaloproteinasas de matriz (5,30). Se ha determinado en diferentes estudios las propiedades antiinflamatorias e inmunomoduladoras de la doxiciclina asociadas a estos efectos (31,32).…”
Section: Ehrlichia Canis and The Effects Of Doxycycline In The Treatmentunclassified
“…One of the theories is the reduction of the oxidative stress, decreasing cytokine levels and inhibiting the activity of matrix metalloproteinases (5,30). The anti-inflammatory and immunomodulatory properties of doxycycline associated with these effects have been determined in different studies (31,32).…”
Section: Sistema Inmunementioning
confidence: 99%